Mary Parker Follett: Pioneer in Management Theory - Sethi, Narendra K. (Academy of Management Journal, 1962)
Features Mary Parker Follett, a social philosopher and a business institutionalist. Principles of organization; Ways to dealing with conflict; Contributions of Follett to the study of modern administrative behavior; Explanation of Follett about delegation of authority; Aspects of leadership.